PARENTS AS TUTORS FIRST AND PRINCIPAL TO CREATE HIGH-QUALITY HUMAN RESOURCES - Kumara, Agus Ria (JURNAL FOKUS KONSELING, 2015)
AbstractThe change of new era means that each individual always evolves.Developments marked with the demands of improving the quality of human resources in its different aspects.Nation character very much dependent on the quality of human resources are.The character of quality need to fostered since an early age.There are two factors that influence character, which is innate from within yourselves sons of and views the children of the world it does possess, such as knowledge, experience, moral principles accepted, guidance, parent-child interaction and briefing.A positive environment will form the positive character also on child.The process begins with the conditions develop the character of the private tua as an influential figure to be a bust children.Â Keywords: character, parent, high-quality human resources